Effects of Negative Pressure Wound Therapy on Levels of Angiopoetin-2 and Other Selected Circulating Signaling Molecules in Patients with Diabetic Foot Ulcer. (28th October 2019) - Hohendorff, Jerzy; Drozdz, Anna; Borys, Sebastian; Ludwig-Slomczynska, Agnieszka H.; Kiec-Wilk, Beata; Stepien, Ewa L.; Malecki, Maciej T.
Abstract : Background and Aims . Diabetic foot ulcers (DFUs) are linked to amputations and premature deaths. Negative pressure wound therapy (NPWT) has been used for DFUs. The mechanism of NPWT's action may be associated with its influence on circulating molecules. We assessed NPWT's effect on the plasma levels of angiopoietin-2 (Ang2), a key regulator of angiogenesis, and its microvesicular receptors (Tie2) as well as the microvesicles (MVs) themselves in DFU patients. Materials and Methods . We included 69 patients with type 2 diabetes mellitus (T2DM) and neuropathic, noninfected DFUs—49 were treated with NPWT and 20 were treated with standard therapy (ST). Assigning patients to the NPWT group was not random but based on DFU characteristics, especially wound area. Ang2 was measured by ELISA in the entire group, while in a subgroup of 19 individuals on NPWT and 10 on ST, flow cytometry was used to measure Tie2+ and the corresponding isotype control (Iso+) and annexin V (AnnV+) as well as total MVs. Measurements were performed at the beginning and after 8 ± 1   days of therapy. Results . Treatment groups were similar for basic characteristics but differed by their median DFU areas (10.3 (4.2-18.9) vs. 1.3 (0.9-3.4) cm 2, p = 0.0001 ). At day 0, no difference was observed in Ang2 levels, total MVs, MV Tie+, and MV AnnV+ between the groups. Ang2 decreased after 8 days in the NPWT group, unlike in the ST group (3.54 (2.40-5.40) vs. 3.32 (2.33-4.61), p = 0.02, and 3.19 ± 1.11 vs. 3.19 ± 1.29   ng / mL, p = 0.98, respectively). No other parameters were identified that may have been influenced by the NPWT treatment. Conclusion . NPWT in T2DM patients with neuropathic, noninfected DFU seems to lead to reduction of the Ang2 level. Influencing the level of Ang2 may constitute one of NPWT-related mechanisms to accelerate wound healing.